Effectiveness of Artocarpus heterophyllus lamk. serum in eliminating dark spot in the guinea pig melasma model due to UV-a exposure - Mas Tiari, Ida Ayu Dwi Putri; Mardiyanti Putri, Ni Putu Kania; Marliani, Ni Luh Setia; Sari, Ni Made Elma Agustini; Malelak, Julia Eva; Adrianta, Ketut Agus (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Indonesia's high UV-A exposure significantly contributes to skin hyperpigmentation conditions such as melasma. This study investigated the effectiveness of Jackfruit (Artocarpus heterophyllus Lamk.) leaf serum in reducing dark spots in a guinea pig model of melasma induced by UV-A radiation. Crude extracts were prepared and purified from Jackfruit (Artocarpus heterophyllus Lamk.) leaves, then formulated into serums at 4% and 5% concentrations. These formulations underwent physical quality evaluations, including organoleptic properties, pH, homogeneity, spread ability, adhesion, and viscosity. Anti-hyperpigmentation effects were assessed using Masson Fontana staining on UV-A-exposed guinea pigs treated for 14 days. The results demonstrated a reduction in melanin content, with mean values of 17.97±1.68 (negative control), 1.17±0.28 (positive control), 3.56±2.77 (4% serum), and 2.56±1.25 (5% serum). Histological analysis showed that fibroblast proliferation and epidermal hyperplasia were significantly reduced with serum treatment. These effects are attributed to the flavonoid content in Jackfruit (Artocarpus heterophyllus Lamk.) leaves, which exhibit antioxidant and anti-melanogenesis properties. In conclusion, Jackfruit (Artocarpus heterophyllus Lamk.) leaf serum, particularly at 5% concentration, is effective in reducing melasma-related hyperpigmentation and may offer a safer alternative to synthetic treatments.